Urban tree structure in parks and sidewalks of San Pedro Garza García, Mexico - Sandoval-García, Rufino (2026)
The objective of this study was to describe the horizontal and vertical structure of urban trees in nine important green areas in San Pedro Garza García, Mexico. In 2024, a census of the trees, shrubs and palms in the previously established areas was carried out, measuring the normal diameter (ND), crown diameter and total height of everyone. Abundance, dominance, frequency and importance value index were estimated, and range-abundance curve, diameter and height class graphs were generated. Ninety-eight species of trees, shrubs and palms were recorded in the nine areas studied, distributed in 35 families. According to their distribution range, 50 species were native and 48 were introduced. The most represented family was Fabaceae, with 15 species, followed by Fagaceae and Pinaceae, both with nine species. Of the six species with the highest importance value, three were native(Fraxinus uhdei, Leucophyllum frutescens and Ehretia anacua) and three were introduced (Quercus virginiana, Pinus eldarica and Leucaena leucocephala, the latter being an invasive exotic). The abundance structure of the plant community is dominated by a few species, suggesting the need for diversification to improve the resilience and functionality of urban ecosystems. The preponderance of trees with small diameters indicates that green areas have been recently reforested. It is recommended to continue using native species and increase diversity in the composition of families, genera and species to strengthen the resilience and sustainability of the plant community.